Formability improvement in Ti-6Al-4 V sheet at room temperature by pulsating hydraulic bulging: experimental and numerical investigations - Ozturk, Osman; Korkmaz, Habip G.; Atas, Gurkan; Aydin, Mevlut; Turkoz, Mevlut; Toros, Serkan; Dilmec, Murat; Livatyali, Haydar; Kotan, Hasan; Halkaci, H. Selcuk (SPRINGER LONDON LTD, 2023)
Ti-6Al-4 V sheets possess limited formability at room temperature due to low ductility with almost no strain hardening. Pressure pulsation during hydroforming may bring significant improvement as an alternative to the widespread solution hot forming. However, much uncertainty exists on the deformation mechanism and effects of pulsating on difficult-to-form materials. In this study, the effect of pulsating pressure on the hydraulic bulge test was investigated to increase the limited formability of the Ti-6Al-4 V sheet at room temperature. Experimental results of thickness distribution and bulge height obtained from the bulge tests were compared with the finite element simulation results. The results show that the tests with pulsation allow a higher thickness reduction with a slightly more homogenous thickness distribution. Pulsation causes a delay in the material's failure resulting in a 15.4% increase in the dome height with a 17% increased burst pressure compared to monotonic loading. The underlying microstructural phenomena of increased formability were elaborated using dislocation estimations, fracture surface analysis, and hardness. Test results suggest that pulsation improves formability by 47% in terms of maximum elongation due to stress relaxation.
Keywords: Sheet metal forming; Pulsating hydroforming; Formability; Ti-6Al-4 V; FINITE-ELEMENT SIMULATION; STRESS-RELAXATION; FLOW-STRESS; ALLOY SHEET; PRESSURE; OPTIMIZATION; DEFORMATION; SPRINGBACK; PARAMETERS; DUCTILITY; Automation & Control Systems; Engineering